RELATIONSHIP BETWEEN PREDICTION READING STRATEGY AND 5TH GRADE STUDENTS’ ACADEMIC ACHIEVEMENT IN ENGLISH IN BOMI COUNTY, LIBERIA - Anyachebelu, Faith E.; Zayzay, Winnifred Lydia Arena (Journal of Early Childhood and Primary Education, 2025)
This study investigated the relationship between prediction reading strategy and 5th grade students’ academic achievement in English in Bomi County, Liberia. This study adopted the correlational survey research design. The population for the study comprises of comprises 314 public primary school teachers in 71 public primary schools in Senjeh District of Bomi County Northwestern Liberia 2022/2023 academic session. The sample for the study comprises approximately 142 teachers The instrument for data collection is a 15-item structured questionnaire which was titled the Use of Prediction Reading Strategy Questionnaire (UPRSQ). The questionnaire is structured from a pool of literature on a 4-point Likert scale of strongly agree, agree, disagree and strongly disagree with weighted scores of 4,3,2,1. The questionnaire was validated by three experts one from the department of education foundations (Measurement and Evaluation unit), one from the department of early childhood and primary education both from the Faculty of Education Nnamdi Azikiwe University, Awka. One validates was a classroom teacher in the Senjeh District of Bomi County, Liberia. The reliability of the instrument was established using the Cronbach alpha statistics, and yielded a reliability coefficient of 0.85. The achievement scores of the 5th grade pupils in reading comprehension and grammar were collected from the classroom teachers and used in this study. Data was collected through the use of google form and emails. Data collected was analyzed using Pearson product moment correlation coefficient (Pearson r) and linear regression analysis. The findings of the study revealed that a moderate positive relationship exists between the use of prediction reading strategy and 5th grade students’ academic achievement in reading comprehension; a low positive relationship exists between the use of prediction reading strategy and 5th grade students’ academic achievement in grammar in Senjeh District of Bomi County, Liberia. The hypothesis tested revealed that there is a significant relationship between use of prediction reading strategy and 5th grade students’ achievement in reading comprehension; also, there is a significant relationship between use of prediction reading strategy and 5th grade students’ achievement in grammar in Senjeh District of Bomi County, Liberia. Conclusions were made and it was recommended among others that teachers should endeavour to use strategies like prediction reading strategy which was reported to correlate with the subjects taught at the primary school level.